Heat shock protein 90-sheltered overexpression of insulin-like growth factor 1 receptor contributes to malignancy of thymic epithelial tumors - Breinig, Marco; Mayer, Philipp; Harjung, Andreas; Goeppert, Benjamin; Malz, Mona; Penzel, Roland; Neumann, Olaf; Hartmann, Arndt; Dienemann, Hendrik; Giaccone, Giuseppe; Schirmacher, Peter; Kern, Michael A.; et al. (Clinical cancer research, 2011)
Purpose: The underlying molecular mechanisms of thymic epithelial malignancies (TEMs) are poorly understood. Consequently, there is a lack of efficacious targeted therapies and patient prognosis remains dismal, particularly for advanced TEMs. We sought to investigate protumorigenic mechanism relevant to this understudied cancer.Experimental Design: Recently established cell lines derived from thymic epithelial tumors were used as a model system. The antitumor activity of specific heat shock protein 90 (Hsp90) inhibitors was investigated by an analysis of cell viability, cell cycle, and apoptosis using MTT-assays and flow cytometry. Western blotting was used to investigate the altered expression of Hsp90 clients. Pharmacological inhibitors against select Hsp90 clients, as well as RNAi, were employed to test the relevance of each client independently. Tissue microarray analysis was performed to match the in vitro findings with observations obtained from patient-derived samples.Results: Hsp90 inhibition significantly reduces cell viability of thymic carcinoma cells, induces cell cycle arrest and apoptosis, and blocks invasiveness. Hsp90 inhibition triggers the degradation of multiple oncogenic clients, for example insulin-like growth factor 1 receptor (IGF-1R), CDK4, and the inactivation of PI3K/Akt and RAF/Erk signaling. Mechanistically, the IGF/IGF-1R-signaling axis contributes to the establishment of the antiapoptotic phenotype of thymic cancer cells. Finally, IGF-1R is overexpressed in advanced TEMs.Conclusions: We have unraveled a novel protumorigenic mechanism in TEMs, namely Hsp90-capacitated overexpression of IGF-1R, which confers apoptosis evasion in malignant thymic epithelial cells. Our data indicate that Hsp90 inhibition, which simultaneously blocks multiple cancer hallmarks, represents a therapeutic strategy in TEMs that may merit evaluation in clinical trials.